THE INFLUENCE OF PRICE, PRODUCT QUALITY AND LOCATION ON THE PURCHASE DECISION OF LOCAL FOOD SNACKS AND SOUVENIRS FOR THE SUKAMAJU FARMING GROUP, AJAOBAKI VILLAGE, MOLLO UTARA DISTRICT, SOUTH TIMOR REGENCY - Susanto Susanto; Ronaldo Ismail Abi; Nonik Kusuma Ningrum (Universitas Muhammadiyah Makassar, 2022)
This research aims to find out how much influence the variable price, product quality and location on the decision to buy Snacks and Souvenirs from Local Food Sukamaju Farmers Group Ajaobaki Village. This research is a quantitative study using the SPSS program with a sample number of 200 respondents who are customers and consumers of Snack and Souvenir Products from Local Food Sukamaju Farmers Group who have bought and consumed Snack and Souvenir products once or more. The results of these findings showed that product quality and location variables had a significant effect on purchasing decisions. While the price variable indicates that there is no significant influence on the purchase decision. The implications of this research can be a reference for business owners in formulating strategies to improve the purchase decision of Snacks and Souvenirs of Sukamaju Farmers Group related to price, product quality and location.